Early subjective cognitive disorders and their relationship with chronic diseases, subjective hearing difficulties, burnout syndrome, and depression among middle-aged women - Pečeliūnienė, J.; Žukauskaitė, I.; Dovydėnas, V. (Neurologijos seminarai, 2021)
Introduction. With the increase in cognitive impairment among young people, it is important to timely identify and modify risk factors.The aim of the study was to evaluate early cognitive disorders in relationship with subjective hearing disorders, burnout syndrome, and depression among middle-aged women.Methods. The study involved 310 women aged 26 to 59 years (M=38.6). An online survey was created. Respondents filled in the Cognitive Failures Questionnaire (CFQ), Subjective Cognitive Complaints (SCCs) questionnaire, Shirom-Melamed Burnout Measure (SMBM), and Geriatric Depression Scale (GDS). Sociodemographic factors, addictions, subjectively reported presence of chronic diseases, and subjective hearing disorders were registered by the study questionnaire. Student’s t-test, Chi-square test, Fisher’s exact test, and logistic regression analysis (LRA) were used for data analysis.Results. 34 females (11%) had subjective cognitive failures (CF+ group) and 276 (89%) had not (CF- group). 28.7% of respondents had subjective cognitive complaints (SCC+ group) and 71.3% had not (SCC- group). 23 females (7.4%) had depression and 62 females (20%) were likely to be depressed. 34 (11%) females had significant symptoms of burnout. 30.6% (N=95) self-reported having chronic diseases. 14.84% of females had subjective hearing disorders. The CF+ group had higher GDS scores than the CF- group (M=6.88 vs. M=3.78, p